Using Markets to Measure Pre-War Threat Assessments: The Nordic Countries Facing World War II - Daniel Waldenström; Bruno S. Frey (Research Institute of Industrial Economics (IFN), 2006)
Nordic historians have asserted for a long time that in the Nordic countries only few people, if any, perceived increased threats of war prior to the World War II outbreak. This would explain, and possibly excuse, why their governments did not mobilize their armies until it was too late. This paper questions this established notion by deriving new estimates of widely held war threat assessments from the fluctuations of sovereign market yields collected from all Nordic bond markets at this period. Our results show that the Nordic contemporaries indeed perceived significant war risk increases around the time of major war-related geopolitical events. While these findings hence question some, but not all, of the standard Nordic World War II historiography, they also demonstrate the value of analyzing historical market prices to reassess the often tacit views and opinions of large groups of people in the past.
Keywords: C22; G14; N01; N44; 330; Structural breaks; Sovereign debt; Capital Markets; Historiography; Cliometrics; World War II; Krieg; Finanzmarkt; Öffentliche Anleihe; Strukturbruch; Cliometrie; Geschichte; Dänemark; Finnland; Norwegen; Schweden